The Ur III administrative texts from Puzrish-Dagan kept in the Harvard Museum of the Ancient Near East - Liu, Changyu (Harvard semitic studies, 2021)
Introduction -- Catalogue of texts -- Chronological list -- Catalogue of seal impressions -- List of texts already published -- Classification of texts according to text formula -- Texts nos. 1-689.